2021
DOI: 10.32400/iaj.33169
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors affecting audit delay in manufacturing and financial companies listed on IDX

Abstract: The study aims to identify and analyze the factors affecting the audit delay. The study includes a quantitative study using secondary data obtained from the company’s financial statement. The study’s population constituted the entire manufacturing and finance companies listed on the Indonesia Stock Exchange during the year 2018-2019. The sample is collected by using purposive sampling over the listed companies in the criteria that the company publishes the audited financial report as of December 31 and also sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Research (David M & Butar, 2020) found that the completion of the audit will be long enough if the company's branches are many because external auditors must be careful in conducting examinations of consolidated financial statements. Research (Muna & Lisiantara, 2021) found that the number of branches is an indicator of the complexity of the inspection object, so it will affect audit delay. Research (Dwiyanti et al, 2022) found that the number of branches determining the audit scope and scope will affect audit delay.…”
Section: Discussionmentioning
confidence: 99%
“…Research (David M & Butar, 2020) found that the completion of the audit will be long enough if the company's branches are many because external auditors must be careful in conducting examinations of consolidated financial statements. Research (Muna & Lisiantara, 2021) found that the number of branches is an indicator of the complexity of the inspection object, so it will affect audit delay. Research (Dwiyanti et al, 2022) found that the number of branches determining the audit scope and scope will affect audit delay.…”
Section: Discussionmentioning
confidence: 99%
“…If the company's profit is high, the auditor will request a financial statement audit to be carried out more quickly (Indriani, 2020). High profitability levels demand faster financial audits (Muna & Lisiantara, 2021). Therefore, companies with high liquidity tend to report their finances quickly (Nuraini et al, 2023).…”
Section: Theoretical Basis and Hypothesis Developmentmentioning
confidence: 99%
“…Concerning agency theory, if the company's data has been audited by a KAP affiliated with the Big Four KAPs, and has a good reputation and quality, it will make service users trust the auditor more, so management will not replace it. Studies Wijasari & Ary (2021), David Butar (2020), and Muna & Lisiantara (2021) report that KAP's reputation negatively influences audit report lag. H4: KAP reputation has a negative effect on audit report lag.…”
Section: Reputation Of Public Accounting Firm and Audit Report Lagmentioning
confidence: 99%
“…With a good reputation owned by the KAP, it will make it carry out its duties professionally, assist the company in completing audit reports on time and reduce the possibility of audit delays. Studies Wijasari &Ary (2021), andMuna &Lisiantara (2021) explain that KAP's reputation negatively influences audit report lag. Meanwhile, according to research from Armand et al (2020) explaining, the reputation of KAP does not affect audit report lag.…”
Section: Introductionmentioning
confidence: 99%